Tim Gates letter to Thomas H. Kent regarding bird sightings, June 2, 1980 - Gates, Timet al (1980)
Field notes contributed by Tim Gates in a letter to Thomas H. Kent, June 2, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1980. Epson - sheet feed/flatbed